Premenstrual syndrome and premenstrual dysphonic disorder - Khajehei, Marjan; Behroozpour, E.; Hajizadeh, N. (WASET, 2010)
Premenstrual syndrome is a combination of physical and emotional disturbances that occur after a woman ovulates and ends with menstruation. More than 200 symptoms have been known as the symptoms of PMS. About 20% to 80% of women in reproductive years experience these disturbing symptoms. A more severe form of PMS, known as premenstrual dysphoric disorder (PMDD)occurs in a smaller number of women and leads to significant loss of function because of unusually severe symptoms. It is believed that 2% to 6% of women suffer PMDD. Women, who have had PMDD, are at increased risk for depression after menopause. Recording a complete medical history and doing careful physical and pelvic examination in addition to having a menstrual diary can help diagnose PMS/PMDD. Although there is no consensus on the cause of PMS and PMDD, biological, psychological, environmental, and social factors all seem to play a part. Several approaches and diagnostic tools have facilitated widespread recognition of PMS and PMDD and these psychological issues have attracted a broad range of research interest in the treatment and management of the symptoms. Although there is no "cure" for PMS and PMDD at this time, there are many options in managing signs and symptoms.